Swedish Plectida (Nematoda). Part 6. Neocamacolaimus parasiticus gen. n., sp. n. - Holovachov, Oleksandr; Boström, Sven (Zootaxa, 2014)
A new genus Neocamacolaimus gen. n., with one new species N. parasiticus gen. n., sp. n. is described from the benthic polychaete Sphaerosyllis cf. hystrix collected in the Skagerrak off the west coast of Sweden. Neocamacolaimus gen. n. is placed in the family Camacolaimidae and is particularly characterised by having annulated cuticle with lateral alae; setiform cephalic sensilla located at level with amphids; amphidial fovea ventrally spiral; buccal cavity without armament; pharynx muscular; nerve ring located at base of pharynx; male reproductive system diorchic with outstretched testes; spicules weakly arcuate with straight manubrium; gubernaculum absent; alveolar supplements located in the pharyngeal region; tubular supplements absent; tail conoid; caudal glands and spinneret present. Juveniles of this genus are particularly characterised by their parasitic lifestyle and the following unique morphological features: lips form a dorso-ventrally elongated perioral disc with internal sclerotizations: one midventral and two dorsosublateral (right and left); cephalic sensilla setiform, subventral sensilla are noticeably longer than the subdorsal ones; intestine extends posterior to rectum and anal opening, forming a post-anal pouch.